EFFICACY OF HYDROGEN PEROXIDE FUMIGATION IN IMPROVING DISINFECTION OF HOSPITAL ROOMS AND REDUCING THE NUMBER OF MICROORGANISMS - Humayun, Tabish; Qureshi, Ahmed; Al Roweily, Salha Falah; Carig, Josephine; Humayun, Farhat (Journal of Ayub Medical College Abbottabad, 2019)
Background: The hospital acquired infection are very common in any health care setting due to certain bacteria, viruses and fungi. In order to find out a solution to this problem, this preliminary study was designed to find out the efficiency of hydrogen peroxide fumigation in reducing the number of microorganisms and improving the disinfection of hospital rooms. It was a prospective cross over study, conducted in Arar Central Hospital, North region, Arar, Kingdom of Saudi Arabia, for the period of one year, from March 2015 to February 2016. Objective of the study was to determine the efficacy of hydrogen peroxide fumigation in the improvement of disinfection of hospital rooms. Methods: A total of 10 environmental samples were taken immediately after the patient was discharged (R1), 10 after terminal cleaning (R2), and 10 after the Bioxeco hydrogen peroxide fumigation (R3) in 20 different rooms of the hospital including ICU, general medical wards and operating rooms. (T=600) Results: Almost 95% rooms cultured (environmental surfaces) after patient was discharged (R1) revealed microorganism growth, 80% after terminal cleaning (R2) and 2% after Bioxeco Hydrogen Peroxide fumigation revealed growths of microorganisms like bacteria and fungi on the culture plates (R3). The highest rate of room contamination was found in the rooms where the patients had stayed for a longer period of time. Conclusions: Hydrogen peroxide fumigation has been proved to be an efficient disinfectant in a health care setting. Keywords: Decontamination; disinfection; health care setting; fumigation; vaporized hydrogen peroxide